Effects of Steam-To-Biomass Ratio and Temperature in Gasification on The Methanol Conversion and Selectivity: A Simulation Study of Biomass to Methanol - Rahma Muthia; Muhammad Raihan Pratama (Universitas Negeri Semarang, 2023)
Gasification is an attractive pathway for valorizing waste and biomass as it can deal with a wide range of feedstocks yielding gaseous products that be converted further to valuable biofuels and chemicals. While many previous studies commonly discussed the effects of gasification operating parameters, such as operating conditions, biomass feedstocks and gasifying agents, on syngas compositions, fewer studies evaluated the effects of gasification process parameters on final products derived from syngas. Essentially, performing an integrated assessment of the biomass-to-product conversion gives a thorough understanding of the biomass processing and provides one with useful heuristics for the conversion of biomass to valuable chemicals. This study evaluates the effects of steam-to-biomass ratio (S/B = 0.3 – 0.7) and gasification temperature (Tgasif = 900℃ – 1,100℃) on the methanol production by performing simulations in the Aspen Plus v.11 process simulator. The kinetically controlled reactions model was considered in the methanol synthesis unit to mimic its actual process condition and to take into account the possibility of the side product formation. The outcome of this study recommends that the steam-to-biomass ratio gives more notable effects on the gasification distribution products and the conversion of syngas to methanol than those given by the gasification temperature. While, the reaction selectivity to methanol remains high, and it is not sensitive to the change of steam-to-biomass ratios and gasification temperatures.